P‐9.12: Hybrid Full Color Micro‐LED Displays with Quantum Dots. (28th November 2018) - Wei, Feng; Li, Shang; Lu, Tao; Liu, Yibo; Wang, Ruoning; Yan, Siwu; Liu, Zhaojun
Abstract : Micro‐LED has attracted increasing attention in recent years for its superior advantages of self‐emission, long lifetime, low power consumption, fast response and high brightness. Quantum dot is a kind of nanoparticle with a diameter of 1 10nm. As photoluminescence quantum dot absorbs light over a wide wavelength range and has a narrow emission spectra, it is a perfect color conversion material for Micro‐LED displays when compares with phosphors. In this paper, we propose a full color displays with high brightness blue Micro‐LED array, using red and green photoluminescence quantum dot as the color conversion material. The photoluminescence quantum dot‐based full color Micro‐LED displays we design has a wide‐color‐gamut and low energy consumption.